Freedom, Creativity, the Self, and God: Between Rabbi Kook and Bergson’s Lebensphilosophie - Amati, Ghila (2024)
In this essay, I examine the intersection between the concepts of freedom, the self, God, and creativity in the works of one of the most prominent twentieth-century Jewish thinkers, Rabbi Abraham Isaac HaCohen Kook (1865-1935), exploring his use of these concepts through the lens of the Lebensphilosophie of the French philosopher Henri Bergson (1859-1941). I first draw a historical and thematic parallel between Bergson’s and Kook’s philosophies that to date has not been considered extensively. I then argue that five different interpretative puzzles related to the topic of freedom in Kook’s teachings can be explained against the background of Bergson’s thought. This Bergsonian interpretation enables the reader to appreciate in what way different aspects of Kook’s thought—the metaphysical, ethical, epistemological, and theological—are interconnected and can be understood as an organic whole. I thereby show that the Bergsonian philosophical and systematic models are an important, and yet unexplored, interpretative tool for the study of Kook’s theological and philosophical thought.
Keywords: Henri Bergson; Rabbi Kook; authentic self; Creativity; Freedom; modern Orthodoxy; Philosophy of Life; Religious Zionism